Dampak Teknologi Absensi Biometrik pada Efektivitas Kerja – Sebuah Tinjauan Literatur - Veronika, Veronika; Setiawan, Amelia; Djajadikerta, Hamfri (Universitas Pahlawan Tuanku Tambusai, 2024)
Work effectiveness is the ability to do something appropriately based on predetermined goals. Work effectiveness can be influenced by several factors, one of which is employee discipline. Disciplined employees tend to be able to complete their work well and on time. One way to measure employee discipline is with an attendance system. The attendance system that is widely used today is biometric attendance technology because it is considered more reliable and accurate than manual attendance systems. The influence of biometric attendance technology on work effectiveness and employee discipline will be proven through a literature study method that discusses 15 selected articles. The criteria for the selected articles are articles published in 2018-2024. From the articles that have been researched, the results show that biometric attendance technology has an effect on employee discipline, and employee discipline has an effect on employee work effectiveness.